The International Sepsis Forum's controversies in sepsis: how will sepsis be treated in 2051? - Abraham, Edward (BioMed Central, 2002)
Great advances have been made in describing the intracellular pathways and genes that are activated by bacterial products. New definitions and therapies for sepsis will be based on such cellular and genetic alterations. In particular, in 2051 sepsis will no longer be defined simply as a clinical constellation of findings, but rather will be divided into different entities dependent on the intracellular cascades or genes activated. Similarly, therapies will be specifically directed at such functional genetic or biochemical alterations, thereby permitting more rational therapy of specific cellular abnormalities in infected patients. Supportive care will also have advanced by 2051, allowing for less iatrogenic harm to critically ill septic patients. Finally, a better appreciation of the cellular and genetic pathways that are activated in patients will permit an improved understanding of prognosis in critically ill infected patients, allowing more appropriate use of therapies.